2017
DOI: 10.1021/jacs.7b07902
|View full text |Cite
|
Sign up to set email alerts
|

Operando Phonon Studies of the Protonation Mechanism in Highly Active Hydrogen Evolution Reaction Pentlandite Catalysts

Abstract: Synthetic pentlandite (FeNiS) is a promising electrocatalyst for hydrogen evolution, demonstrating high current densities, low overpotential, and remarkable stability in bulk form. The depletion of sulfur from the surface of this catalyst during the electrochemical reaction has been proposed to be beneficial for its catalytic performance, but the role of sulfur vacancies and the mechanism determining the reaction kinetics are still unknown. We have performed electrochemical operando studies of the vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
69
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 27 publications
(34 reference statements)
7
69
1
7
Order By: Relevance
“…[19] Diese Oberflächen bestehen meist aus verschiedenen Eisen-und Nickelsulfiden sowie oxidischen Fe 3+ -Spezies und Ni(OH) 2 , wie durch Rçntgenphotoelektronenspektroskopie (XPS) nachgewiesen wurde.D ennoch wurde kein deutlicher Einfluss auf die Wasserstofferzeugung fürd ie verwendeten Proben beobachtet. [16,18,19] Dieser Effekt wird auch in Abbildung 3A ersichtlich. [16,18,19] Dieser Effekt wird auch in Abbildung 3A ersichtlich.…”
Section: Methodsunclassified
See 3 more Smart Citations
“…[19] Diese Oberflächen bestehen meist aus verschiedenen Eisen-und Nickelsulfiden sowie oxidischen Fe 3+ -Spezies und Ni(OH) 2 , wie durch Rçntgenphotoelektronenspektroskopie (XPS) nachgewiesen wurde.D ennoch wurde kein deutlicher Einfluss auf die Wasserstofferzeugung fürd ie verwendeten Proben beobachtet. [16,18,19] Dieser Effekt wird auch in Abbildung 3A ersichtlich. [16,18,19] Dieser Effekt wird auch in Abbildung 3A ersichtlich.…”
Section: Methodsunclassified
“…[18] Diese Berechnungen wurden experimentell mittels kernresonanter,i nelastischer Rçntgenstreuung untermauert. Hier findet ein korrosiver Alterungsprozess statt.…”
Section: Methodsunclassified
See 2 more Smart Citations
“…[1] Among these parameters,t he catalyst structure and chemical state are of particular importance. [7,8,16,21,[30][31][32][33][34][35][36] However,t he presence of (100) facets is not the only factor responsible for the superior activity and selectivity of cubeshaped Cu catalysts,w ith surface roughness,s ubsurface oxygen and Cu I species or Cu/Cu I interfaces formed and/or stabilized under reaction conditions also playing av ery important role. [20][21][22][23][24][25][26][27][28][29] Previous studies [9][10][11] on Cu single crystals have shown the improved C À Cc oupling performance of (100) facets,w hich was further confirmed by the high selectivity towards ethylene observed on cube-shaped Cu catalysts.…”
mentioning
confidence: 99%